"Echoes of a Proud Nation": Reading Kahnawake's Powwow as a Post-Oka Text - Blundell, Valda (Canadian Journal of Communication, 1993)
Abstract: After presenting one history of North American powwows as sites where aesthetic forms are deployed to transform meanings about aboriginal peoples, an analysis is offered of the powwow produced by the Kahnawake Mohawk a year after their involvement in the Oka crisis. Résumé: Cet article présente d'abord une histoire des powwows nord-américains comme lieux de déploiement de formes esthétiques qui modifient le sens et la signification des peuples autochtones. L'article analyse ensuite le powwow des Mohawks de Kahnawake qui a eu lieu un an après la crise d'Oka.
Number: 3
Keywords: Cultural producers

Une approche sémiologique du powwow contemporain canadien - Blundell, Valda (Recherches amérindiennes au Québec, 1985)